PERSEPSI MASYARAKAT TERHADAP LARANGAN PERNIKAHAN PADA BULAN SURO DALAM ADAT JAWA DI DESA RUMBAI JAYA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Lestari, Ayu; Hambali, Hambali; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the beliefs of the ancestors of Rumbai Jaya Village people who are hereditary that is still believing in the existence of bad dates and full of bad luck (disadvantaged), namely dating in the month of Suro so that many people avoid the month of Suro when they will implement the month of Suro major events including weddings. This research formulated the problem in "What is the Community's Perception of the Suto Month and the Prohibition of Marriage in Suro Month in Javanese Customs in Rumbai Jaya Village, Kempas District, Indragiri Hilir Regency". The purpose of this study was to determine "Community Perception of Suro Month and Marriage Prohibition in Suro Month in Javanese Customs in Rumbai Jaya Village, Kempas District, Indragiri Hilir Regency". The method in this research is descriptive qualitative with data collection techniques through observation, interviews and questionnaires. Determination of the research sample through a sampling area (Sampling area), namely sampling by region, 30 people consisting of 5 informants, namely elders/village elders and 25 respondents, namely predetermined communities. The results of this study are: First, people's perceptions about the month of Suro is a sacred month because in this month many people do tirakat or some kind of ritual for various purposes, suro month is the new year for the Javanese tribe which coincides with the month of Muharram. secondly, people's perception of marriage in the month of suro is that marriage in the month of Suro is prohibited and may not be carried out, so the conclusion is that the community still adheres to ancient traditions and beliefs about the prohibition of marriage in the month of Suro.Keywords: Community Perception, Prohibition of Marriage Suro Month